Surface depletion induced quantum confinement in CdS nanobelts - Li, Dehui (2013)
We investigate the surface depletion induced quantum confinement in CdS nanobelts beyond the quantum confinement regime, where the thickness is much larger than the bulk exciton Bohr radius. From room temperature to 77 K, the emission energy of free exciton A scales linearly versus 1/L2 when the thickness L is less than 100 nm, while a deviation occurs for those belts thicker than 100 nm due to the reabsorption effect. The 1/L2 dependence can be explained by the surface depletion induced quantum confinement, which modifies the confinement potential leading to a quasi-square potential well smaller than the geometric thickness of nanobelts, giving rise to the confinement effect to exciton emission beyond the quantum confinement regime. The surface depletion is sensitive to carrier concentration and surface states. As the temperature decreases, the decrease of the electrostatic potential drop in the surface depletion region leads to a weaker confinement due to the decrease of carrier concentration. With a layer of polymethyl methacrylate (PMMA) passivation, PL spectra exhibit pronounced red shifts due to the decrease of the surface states at room temperature. No shift is found at 10 K both with or without PMMA passivation, suggesting a much weaker depletion field due to the freezing-out of donors.